The English myrror. A regard wherein al estates may behold the conquests of enuy: containing ruine of common weales, murther of princes, cause of heresies, and in all ages, spoile of deuine and humane blessings, vnto which is adioyned, enuy conquered by vertues. Publishing the peaceable victories obtained by the Queenes most excellent Maiesty, against this mortall enimie of publike peace and prosperitie, and lastly a fortris against enuy, builded vpon the counsels of sacred Scripture, lawes of sage philosophers, and pollicies of well gouerned common weales: wherein euery estate may see the dignities, the true office and cause of disgrace of his vocation. A worke safely, and necessarie to be read of euerie good subiect. / By George Whetstones Gent. Malgre. Seene and allowed. [electronic resource] : (1586)
Summary goes here